Ecoprint sebagai Alternatif Produk Fashion Ramah Lingkungan pada UMKM Berbasis Ekonomi Kreatif di SD Negeri 040479 Perteguhen - Asryatun Nisa br Ginting; Nur Azizah Nasution; Aflah Muhajir; Robbani Hafiz; Silvia Tabah Hati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This community service program aims to introduce ecoprint as an alternative environmentally friendly fashion product and encourage the development of alternative economy-based MSMEs at SD Negeri 040479 Perteguhen. The program was carried out in several stages, namely socialization of the concepts of sustainable fashion and alternative economy, training in ecoprint techniques using natural materials such as teak leaves, cassava leaves, and bougainvillea flowers, as well as assistance in production and product development. Participants in the activity consisted of teachers, parents, and members of the community around the school who were interested in the development of creative MSMEs. The results of the activity showed an increase in participants’ understanding of the impact of the fashion industry on the environment and the importance of using environmentally friendly materials. Participants also demonstrated improved skills in ecoprint product manufacturing, from fabric preparation and motif arrangement to color fixation. The resulting products, such as cloth bags, scarves, and tablecloths, are aesthetically pleasing, unique, and have the potential to be sold as valuable local products. In addition, this activity encouraged participants’ creativity in creating a variety of motifs and colors, as well as building awareness of the importance of sustainable innovation. From a socio-economic perspective, this activity opens up opportunities for the development of local MSMEs through the sustainable use of natural resources and the application of alternative economic principles. The formation of a creative community involving schools and the community demonstrates synergy in the development of environmentally-oriented businesses. This activity is expected to become a model for the development of creative MSMEs based on eco-friendly and local resources, while supporting the principles of sustainable development and responsible consumption and production.